2010
DOI: 10.1210/jc.2009-2130
|View full text |Cite
|
Sign up to set email alerts
|

Lower Dose Prednisone Prevents Radioiodine-Associated Exacerbation of Initially Mild or Absent Graves’ Orbitopathy: A Retrospective Cohort Study

Abstract: Lower doses of oral prednisone (about 0.2 mg/kg bw) are as effective as previously reported doses (0.3-0.5 mg/kg bw). A shorter treatment period (6 wk) is probably sufficient. The increase in bw is less using lower doses of prednisone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 18 publications
(23 reference statements)
0
57
0
4
Order By: Relevance
“…As 1989, it has been proposed that a short course of systemic corticosteroid treatment may prevent RAI-induced exacerbation of GO. Steroid prophylaxis has been carried out using very low doses of prednisone (0.2 mg/kg body weight), given 1 day after RAI therapy, and gradually tapered down and withdrawn after 6 weeks, which has been shown to be effective in a study in Italy (42) but not in a recent study on Japanese patients (43). Alternatively, methylprednisolone can be administered intravenously at the dose of 500 mg weekly for 2 weeks followed by another two weekly infusions of 250 mg (cumulative dose of 1.5 g) (40).…”
Section: Current Guidelines For Treatment Of Thyroid Dysfunction In Pmentioning
confidence: 99%
See 1 more Smart Citation
“…As 1989, it has been proposed that a short course of systemic corticosteroid treatment may prevent RAI-induced exacerbation of GO. Steroid prophylaxis has been carried out using very low doses of prednisone (0.2 mg/kg body weight), given 1 day after RAI therapy, and gradually tapered down and withdrawn after 6 weeks, which has been shown to be effective in a study in Italy (42) but not in a recent study on Japanese patients (43). Alternatively, methylprednisolone can be administered intravenously at the dose of 500 mg weekly for 2 weeks followed by another two weekly infusions of 250 mg (cumulative dose of 1.5 g) (40).…”
Section: Current Guidelines For Treatment Of Thyroid Dysfunction In Pmentioning
confidence: 99%
“…Several randomized clinical trials found a De novo occurrence or progression of GO after RAI treatment with or without steroid prophylaxis (39,40,41,42,43) Postablation hypothyroidism induces progression of GO (44,45) Stabilization of GO after total thyroid ablation (thyroidectomy followed by RAI treatment)…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…This detrimental effect is in most cases prevented by concomitant short-term treatment with low doses of oral glucococorticoids (steroid prophylaxis) [28,39,40]. In view of the above considerations and in the absence of well-designed (and extremely difficult to perform) RCTs, selection of the optimal thyroid treatment (antithyroid drugs, radioiodine, thyroidectomy, thyroidectomy followed by radioiodine treatment) in patients with GO is still a matter of argument and more an expert opinion than an evidence-based choice [36].…”
Section: Preventionmentioning
confidence: 99%
“…Un metaná-lisis 29 , que incluye pacientes adolescentes, mostró que el radioyodo tiene un efecto adverso sobre la OG en 15-20% de los casos, no obstante este riesgo puede disminuirse con el uso de glucocorticoides profilácticos 30 . El mecanismo por el cual esto ocurre es probablemente una exacerbación de la respuesta autoinmune, debido a la liberación brusca de antígenos, secundaria a la acción citolítica del radioyodo en las células foliculares del tiroides.…”
Section: Radioyodounclassified